Identification of Environmental Law Enforcement Strategies for the Millennial Generation (Publication Review Study) - Manullang, Sardjana Orba (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
Environmental law enforcement in Indonesia is not a new issue, but it is a global issue that requires real work from the entire world population. Among the most prominent issues include deforestation, reduced biodiversity, damage to coral reefs, lack of fish populations, reduced land, decreased agricultural production, rural decline, shrinking water resources, flooding, poor irrigation infrastructure, declining quality of fishery water, and encroachment: forests, expansion of agriculture. We have reviewed 50 scientific papers that discuss the issue of the application of environmental law in order to manage the issues above. We search for data for our analysis as data findings through digital applications on databases such as Google Book, Sagepub, ResearchGate, and Taylor France. The study begins with an evaluation and coding system and concludes with a complete in-depth interpretation under a phenomenological approach. Thus, this finding becomes a reference for many people who want to examine issues regarding the application of environmental law in Indonesia for the millennial generation.